The Effect of the Quizizz Game on Increasing Motivation and Social Studies Learning Outcomes at the Junior High School Level - Kartini, Agustina; Sriyanto, Sriyanto (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2023)
This study aims to determine the effect of Quizizz games on increasing motivation and social studies learning outcomes for class VII students of SMPN 7 Purwokerto. This experimental research design uses two groups, namely the experimental group and the control group. The data collection technique used interviews, tests (pre-test and post-test), and observation with a sample of 74 students from 286 students from class VII SMP N 7 Purwokerto. The purposive sampling technique showed that the class used as the control class was class VIIB, with a total of 34 students. The treatment was given using traditional learning methods. Class VII A is used as an experimental class with the learning process using the Quizizz learning application. Based on the results of research conducted by Quizizz, learning media can be declared capable of increasing student motivation and learning outcomes. The effect of Quizizz learning media on increasing motivation and learning outcomes using the test declares the Wilcoxon value of Asymp. The sign (2-tailed) is 0.000. Because the Asymp. Sign (2-tailed) is less than 0.05, then Ho is rejected, and Ha is accepted, so it is concluded that the use of learning media based on Quizizz educational games has an effect on increasing motivation and learning outcomes of social studies class VII students of SMPN 7 Purwokerto.